Morbidities among Eclamptic Women of Lower Socioeconomic Community in a Selected Area of Bangladesh (Bangladesh Medical Journal, 2021)
Eclampsia is a serious obstetric emergency with new onset of grand mal seizure during pregnancy or postpartum women having signs symptoms of pre-eclampsia. The sequel of severe pre-eclampsia and eclampsia includes organ failure, loss of consciousness and finally loss of lives of both mother and fetus. This study aimed to evaluate morbidity of eclamptic women at lower socioeconomic community in a selected area of Bangladesh. This descriptive cross sectional study was conducted at Sheikh Hasina Medical College Hospital (SHMC.T) of Tangail district during the period of January to December 2019. During this period 7918 admitted patients from different sub-districts (Upazilas) of this district in obstetrics ward of SHMC.T were observed and 205 diagnosed eclamptic patients were selected as respondents for this study to detect morbidities. The prevalence rate of eclampsia among the obstetrics patients was 2.6%, where 81% of them were found during antepartum/ intrapartum and rest of them during postpartum period. The mean age of the eclamptic cases was 23.78±4.94 years and more than half of   them were in age group 21-30 years. Most of the cases (84%) were from primary level or able to sign or illiterate and rest was secondary level of education. Mean age of marriage and first pregnancy were 17.81±SD2.19 and 19.39±SD2.5 years respectively, where majority of patients were primigravida. Among the multi gravida about one fourth had 2-4 children, 16.09% had 5-6 children, where 1.46% had ≥7 children and more than three-fourth of cases had 34-37 weeks of gestational period. Among cases 95.1% had hypertension, 94.6% edema, 83.9% convulsion, 39.5% headache with blurring of vision, 22.4% severe abdominal pain, 79.0% proteinuria and 9.76% unconsciousness. Incidence of maternal morbidity during study period was 14.36%, among them 9.4% pulmonary edema, 1.5% renal failure, 0.98% HELLP (Hemolysis, Elevated liver enzyme level and Low Platelet level) syndrome, 0.98% coma and 1.5% placental abruption. Caesarean delivery was 79.2% and 11.70% was detected as postpartum haemorrhage. Among fetal morbidity 19.5% intrauterine growth restriction, 48.8% low birth weight, 39.6% birth asphyxia, and 58.5% preterm baby. During follow up only persistent hypertension was found as morbidity of eclampsia, 19.5%, 9.8% and 7.32% at 2nd week, at 6th week and at 6th months respectively. Regarding health care services 93.7% had available facility and 41.5%, 47.8% and 10.7%  lived in >10 kilometers (kms), 5-10 kms and less than 5 km distance respectively. Regarding MCH services; only 5.9% patient received antenatal care (ANC) ≥4 times; more than half of them incompletely received ANC